Pengaruh Pemberian Pupuk Hayati Mikoriza Terhadap Pertumbuhan Tanaman Tomat (Lycopersicum esculentum Mill) - Pulungan, Ahmad Shafwan S.; Rangkuti, Marlinda Nilan Sari; Rahmi, Nisrina Afiqah (CV.ITTC INDONESIA, 2023)
Mycorrhiza is a type of biological fertilizer that can improve soil health, environmental protection, soil nutrient status and agricultural yields. The demand for tomatoes continues to increase every year along with population growth and in 2021. In order to meet the need for tomato consumption every year, various efforts are being made to continue to increase production through the use of minimal and environmentally friendly output such as the use of mycorrhiza biological fertilizer. This research aims to determine the effect of the use and dosage of mycorrhizal fertilizer on the growth of tomato plants (Lycopersicum esculentum Mill). This research was carried out on Jln Rela, Gg. Danau Toba, No. 16. starting from 10 September 2023 - 11 November 2023. Mycorrhizal fertilizer was given in 2 treatments, namely 5 gr and 10 gr with 2 repetitions each and control (no mycorrhizal fertilizer was given). Providing 10g of mycorrhizal biofertilizer/plant provides the best growth and results for tomato plants with the parameters of plant height and number of leaves.